Long-term safety and tolerability of delamanid-containing regimens in multidrug-resistant and extensively drug-resistant tuberculosis patients in a specialised treatment centre in Berlin, Germany. Issue 6 (3rd December 2020) - Häcker, Brit; Schönfeld, Nicolas; Krieger, David; Otto-Knapp, Ralf; Hittel, Norbert; Pflugmacher, Patricia; Bauer, Torsten
Drug-resistant tuberculosis (DR-TB) is an ongoing challenge for patients and healthcare systems. The World Health Organization (WHO) estimated 484 000 (CI: 417 000–556 000) new multidrug-resistant/rifampicin-resistant tuberculosis (MDR-/RR-TB) cases for 2018 [1]. While new and repurposed drugs show promising results in studies, notified treatment outcomes are still below expectations. Germany, as a low incidence country, had 5429 newly diagnosed TB cases (incidence rate of 6.5 per 100 000), including 118 patients with MDR-TB and eight patients with extensively drug-resistant (XDR-) TB in 2018. These data support the safety and tolerability of delamanid in the treatment of patients with MDR- and XDR-TB, even with drug exposure for longer than 6 months https://bit.ly/3cPQQPS